Staffing Levels and COVID‐19 Cases and Outbreaks in U.S. Nursing Homes - Gorges, Rebecca J.; Konetzka, R. Tamara (Journal of the American Geriatrics Society (JAGS), 2020)
BACKGROUND/OBJECTIVES Nursing homes have experienced a disproportionate share of COVID‐19 cases and deaths. Early analyses indicated that baseline quality was not predictive of nursing home cases, but a more nuanced study of the role of nurse staffing is needed to target resources and better respond to future outbreaks. We sought to understand whether baseline nurse staffing is associated with the presence of COVID‐19 in nursing homes and whether staffing impacts outbreak severity. DESIGN We analyzed Centers for Medicare & Medicaid Services (CMS) facility‐level data on COVID‐19 cases and deaths merged with nursing home and county characteristics. We used logistic regressions to examine the associations of staffing levels from Nursing Home Compare with the outcomes of any COVID‐19 cases and, conditional on at least one case, an outbreak. Among facilities with at least one case, we modeled count of deaths using hurdle negative binomial‐2 regressions. SETTING All nursing homes in the CMS COVID‐19 Nursing Home Dataset with reports that passed the CMS Quality Assurance Check as of June 25, 2020. PARTICIPANTS Residents of nursing homes that met COVID‐19 reporting requirements. MEASUREMENTS A nursing home is defined as having at least one case is if one or more confirmed or suspected COVID‐19 case among residents or staff is reported. Conditional on at least one case, we examine two outcomes: an outbreak, defined as confirmed cases/certified beds >10% or total confirmed and suspected cases/beds >20% or >10 deaths, and the total number of deaths attributed to COVID‐19 among residents and staff. RESULTS A total of 71% of the 13,167 nursing homes that reported COVID‐19 data as of June 14 had at least one case among residents and/or staff. Of those, 27% experienced an outbreak. Higher registered nurse‐hours are associated with a higher probability of experiencing any cases. However, among facilities with at least one case, higher nurse aide (NA) hours and total nursing hours are associated with a lower probability of experiencing an outbreak and with fewer deaths. The strongest predictor of cases and outbreaks in nursing homes is per capita cases in the county. CONCLUSION The prevalence of COVID‐19 in the community remains the strongest predictor of COVID‐19 cases and deaths in nursing homes, but higher NA hours and total nursing hours may help contain the number of cases and deaths.